Cytotoxicity And Cell Deatl-I Mechanisms Of Epipremnum Pinna Tum (L.) Engl. Extracts In T-47d, A Breast Carcinoma Cell Line - Tan, Mei Lan (2003)
In this study, Epipremnum pinnatum (L.) Engl. extracts were shown to exhibit remarkable inhibition against the growth of T-47D, a breast carcinoma cell line. The hexane extract was the most potent (EC5o at 2.870 ug/ml) as compared to the chloroform and methanol extracts (EC5o at 5.590 ug/ml and 6.470 ug/ml, respectively). However, cell death mechanisms elicited by these three extracts were somewhat nonsimilar.